De nuevo sobre Troya y los libros de caballerías: “Aunque tantos años son passados, bien creo aún no será en el mundo de tan grandes hechos perdida la memoria” - Sales Dasí, Emilio José (Troianalexandrina, 2009)
Abstract The “libros de caballerías” were a significant source of diffusion of the Trojan material during the peninsular Renaissance. In the second half of the 16th century, the “libros de caballerías” of entertainment especially favoured the progressive incorporation of Classical subjects. This work analyses the functionality of that tradition in the Castilian genre, used by many authors as a term of comparison, as a source that provides examples of a moral type, as a point of reference in order to emphasise the heroism of their own characters or as an argument to establish a temporary continuity between the Trojan legend and the fabulous chivalric world.